Peran Bahasa Melayu dalam Penyebaran Islam Nusantara: Penelitian - khusnul khotimah; Alya Junisa Khasana (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to analyze the strategic role of the Malay language in the spread of Islam across the Indonesian archipelago. As a lingua franca in Southeast Asia, Malay played a crucial role in facilitating cross-ethnic communication, trade, and Islamic propagation. The research employs a qualitative literature review by examining historical sources, Islamic texts, and classical Malay literature. The results show that Malay functioned not only as a medium of communication but also as a tool for Islamic preaching and education through religious translations, the writing of hikayat, and the use of Jawi script. Literary works such as syair gulung served as effective instruments for transmitting Islamic values among the Malay people. Therefore, the Malay language played a vital role in shaping the cultural and religious identity of the Nusantara community and strengthening the integration between language, culture, and religion in the development of Islamic civilization in Indonesia.